Proceedings of the Companion Publication of the 2014 Annual Conference on Genetic and Evolutionary Computation 2014
DOI: 10.1145/2598394.2611383
|View full text |Cite
|
Sign up to set email alerts
|

Reusing learned functionality in XCS

Abstract: This paper expands on work previously conducted on the XCS system using code fragments, which are GP-like trees that encapsulate building blocks of knowledge. The usage of code fragments in the XCS system enabled the solution of previously intractable, complex, boolean problems, e.g. the 135 bit multiplexer domain. However, it was not previously possible to replace functionality at nodes with learned relationships, which restricted scaling to larger problems and related domains. The aim of this paper is to reu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Such problems are difficult for machine learning algorithms as the search space consists of multiple interacting patterns that are often repeated, which obfuscates the decision boundaries. Based on XCSCFC, Alvarez et al [16] later introduced ruleset functions in CFs in XCSCF 2 to enable the reusability of CFs with learned ruleset functions for the function nodes. This system can solve hierarchical problems, such as 18-bit Hierarchical Mux problem, with transfer learning.…”
Section: B Scalable Lcssmentioning
confidence: 99%
See 2 more Smart Citations
“…Such problems are difficult for machine learning algorithms as the search space consists of multiple interacting patterns that are often repeated, which obfuscates the decision boundaries. Based on XCSCFC, Alvarez et al [16] later introduced ruleset functions in CFs in XCSCF 2 to enable the reusability of CFs with learned ruleset functions for the function nodes. This system can solve hierarchical problems, such as 18-bit Hierarchical Mux problem, with transfer learning.…”
Section: B Scalable Lcssmentioning
confidence: 99%
“…We do not divide the initial subproblems any further although it was demonstrated that CF-based XCSs could learn such functions from even smaller subproblems [16]. Future work with ConCS will explore the intellectually interesting question of "what are smallest axioms that can initialize learning?"…”
Section: Knowledge Managementmentioning
confidence: 99%
See 1 more Smart Citation